The Role of Customary Law in Natural Resource Management in Rural Areas for National Defence and The Preservation of National Sovereignty - Irman Putra; Parluhutan Sagala; Ahmad Jaeni; Aref Fahmi Lubis (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study explores customary law’s role in managing natural resources in rural areas of Indonesia, focusing on its contribution to national defence and the preservation of national sovereignty. Adopting a qualitative approach based on a literature review, this research examines the interactions between customary law, state law, and local practices within the resource management framework. The findings reveal that customary law remains a vital institution in regulating access to and utilization of natural resources despite the challenges posed by modern development policies and globalization. The study identifies various adaptive mechanisms within customary law that allow it to evolve in response to socio-ecological changes, thus supporting sustainable resource management. Furthermore, the research highlights the importance of incorporating customary law into formal policy frameworks to enhance the effectiveness of natural resource management at local and national levels.